Thrombosed External Jugular Vein Aneurysm: a Rare Cause of Neck Mass - Martins, Inês Santiago (2014)
Venous aneurysms are rarely responsible for neck masses, and regarding the neck veins, external jugular vein aneurysms are extremely uncommon, with a few cases reported in the literature. Although most cases are asymptomatic, they may cause pain, be complicated by thrombosis or even rupture. Imaging studies have a role in the diagnosis and surgical planning of this pathology. With emphasis on the imaging techniques, the authors present a case of an external jugular vein aneurysm, initially asymptomatic but thereafter complicated with thrombosis.Keywords: Jugular Veins; Aneurysm; Thrombosis; Tomography, X-Ray Computed; Ultrasonography.